Coaching in restorative justice processe. A diferent visión. - Steele Garza, José Guadalupe; Garza Castillo, Jesús Roberto (Mediaciones Sociales, 2022)
Times In this paper, the issue of restorative justice is addressed from the perspective and instrumentation of coaching, its objectives, benefits and effects that its implementation has on its users. Likewise, the different restorative models will be described, for example, meetings, circles, victim-offender meetings and family conferences. Likewise, the function of the figure of the facilitator specialized in the discipline of coaching will be addressed and the possibility of implementing coaching competencies within the facilitator's training will be proposed, in order to develop the processes in a more effective way. of restorative justice.
Keywords: restorative justice; coaching; ontological coaching